The cat's pajamas - Edwards, Wallace (Toronto, ON ; Tonawanda, NY : Kids Can Press, 2010)
Depicts twenty-six idioms--contextualized within a sentence--with illustrations that bring new meaning to each, and includes explanations of the sayings.
3.6
K-3
K-3
Keywords: English language -- Idioms -- Juvenile literature; English language -- Idioms; English language -- Idioms; Picture books for children